Analysis of Clean Water Distribution Network System and Service Quality on Customer Satisfaction (Case Study of PDAM Tirtanadi, Cemara Branch, Medan City, North Sumatra Province) - Niki Aulia; Wahyu Syarvina (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This study aims to determine the water demand in 2021 in the drainage area of ​​PDAM Tirtanadi, Cemara Branch, Medan City, to determine the quality of services provided by PDAM Tirtanadi Cemara Branch, Medan City in meeting water needs for customer satisfaction. In this study, the author uses descriptive research with qualitative data types, because this research seeks to explain a fact or reality of certain social phenomena as they are and provide a subjective picture of the circumstances or problems that may be encountered. This is in accordance with the type of research that is intended to provide an overview of the clean water network system and service quality of the Regional Drinking Water Company (PDAM) Tirtanadi, Cemara Branch, Medan City. PDAM Tirtanadi produces water for the spruce area of ​​215,878,752 m, and PDAM Tirtanadi, Cemara Branch distributes water of 82,050,000 m, with a total water loss of 75,949,349 m. Based on this data, the water balance of PDAM Tirtanadi, Cemara Branch, Medan City experienced a surplus, which means that the PDAM is able to meet water needs in the Cemara area.